1992
DOI: 10.1161/01.hyp.19.6.743
|View full text |Cite
|
Sign up to set email alerts
|

Calcium, phosphoinositide, and 1,2-diacylglycerol responses of blood vessels of deoxycorticosterone acetate-salt hypertensive rats to endothelin-1.

Abstract: In previous studies a decreased responsiveness to endothelin-1 (ET-1) of conduit arteries and resistance vessels of deoxycorticosterone acetate (DOCA)-salt hypertensive rats was found in comparison with uninephrectomized controls. Decreased isometric force, number of receptors, and inositol phosphate accumulation were reported in the DOCA-salt animals. In the present study effects of ET-1 on cytosolic free calcium, inositol phosphates, and 1,2-diacylglycerol were investigated in blood vessels of DOCA-salt hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…7 - 22 This suggests that, indeed as a consequence of increased production of ET-1 in blood vessels of DOCA-salt hypertensive rats, endothelin receptors are downregulated, resulting in depressed responses to exogenous and probably endogenous endothelin. Because the walls of blood vessels in DOCA-salt rats are significantly hypertrophied and their lumen reduced, vasoconstrictor responses are magnified in resistance vessels, 21 and thus increased production of ET-1 may play a role in the maintenance of hypertension in this model despite depressed responsiveness to ET-1. Because ET-1 is also a potent mitogen, increased vascular production of ET-1 in DOCA-salt hypertensive rats could be in part responsible for the very important vascular hypertrophy present in this hypertensive model.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…7 - 22 This suggests that, indeed as a consequence of increased production of ET-1 in blood vessels of DOCA-salt hypertensive rats, endothelin receptors are downregulated, resulting in depressed responses to exogenous and probably endogenous endothelin. Because the walls of blood vessels in DOCA-salt rats are significantly hypertrophied and their lumen reduced, vasoconstrictor responses are magnified in resistance vessels, 21 and thus increased production of ET-1 may play a role in the maintenance of hypertension in this model despite depressed responsiveness to ET-1. Because ET-1 is also a potent mitogen, increased vascular production of ET-1 in DOCA-salt hypertensive rats could be in part responsible for the very important vascular hypertrophy present in this hypertensive model.…”
Section: Discussionmentioning
confidence: 95%
“…20 We have previously shown that in DOCA-salt hypertensive rats, responses of aorta and large and small mesenteric arteries to exogenous ET-1 are blunted. 7 - 21 Furthermore, binding of ET-1 to mesenteric arteries is decreased, and signal transduction is also blunted in both mesenteric arteries and aorta. 7 - 22 This suggests that, indeed as a consequence of increased production of ET-1 in blood vessels of DOCA-salt hypertensive rats, endothelin receptors are downregulated, resulting in depressed responses to exogenous and probably endogenous endothelin.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the early, persistent reduction in plasma ␣ 1 -AP activity seen is likely in keeping with Ca 2ϩ overload of PBMCs and ventricular tissue and may include other cells and tissues (eg, platelets, erythrocytes, fibroblasts, endothelial cells, and vascular tissue). 51,[53][54][55] A direct effect of ALDOST on cultured lymphocyte [Ca 2ϩ ] i could not be demonstrated. 20 Widespread Ca 2ϩ loading, which may be a response to elevated plasma PTH levels, could explain the systemic induction of oxi/ nitrosative stress.…”
Section: Chhokar Et Al Wasting In Aldosteronism 875mentioning
confidence: 92%
“…6 -10 This was in part explained by downregulation of vascular endothelin receptors, accompanied by a reduction of phospholipase C activity. 6 - 11 We have speculated that downregulation of endothelin receptors could be secondary to exaggerated production of ET-1 in blood vessels of DOCA-salt hypertensive rats. Here, we show that aorta and mesenteric arteries of DOCA-salt hypertensive rats contain greater amounts of immunoreactive ET-1 (ir-ET-1), suggesting that vascular ET-1 may be involved in some forms of hypertension.…”
Section: Increased Endothelin-1 Content In Blood Vessels Of Deoxycortmentioning
confidence: 99%